The Naḥal Tanninim Dam and its Vicinity Final Report of the 2000-2005 Excavation Seasons - Porath, Yosef, 1940- (Jerusalem)
xiii, 389 sayfa
Keywords: “This volume describes the results of the excavations at the Naḥal Tanninim Dam conducted over ten excavation seasons during the years 2000-2005.” --